2020
DOI: 10.1038/s41598-020-73546-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein on the thermogenesis performance of natural rubber matrix

Abstract: Under high-speed strain, the thermogenesis performance of natural rubber products is unstable, leading to aging and early failure of the material. The quality of rubber latex and eventually that of the final products depends among others on the protein content. We found that when the protein is almost removed, the heat generated by the vulcanized rubber increases rapidly. After adding soy protein isolate to the secondary purification rubber, the heat generation of the vulcanized rubber is reduced, and the heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The results revealed the highest efficacy of DPP in reducing the scorch time and cure time of the rubber compounds. This may be attributed to the fact that DPP had a relatively high protein content (~49%), which could accelerate the sulfur vulcanization of the isoprene rubber, according to the literature [ 51 , 52 , 53 , 54 ]. It has recently been reported that proteins decrease the activation energy of the crosslinking process through the formation of coordination interactions between Zn 2+ and amide bonds of proteins, which improves the solubility of Zn 2+ in the matrix and further contributes to the crosslinking reaction [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed the highest efficacy of DPP in reducing the scorch time and cure time of the rubber compounds. This may be attributed to the fact that DPP had a relatively high protein content (~49%), which could accelerate the sulfur vulcanization of the isoprene rubber, according to the literature [ 51 , 52 , 53 , 54 ]. It has recently been reported that proteins decrease the activation energy of the crosslinking process through the formation of coordination interactions between Zn 2+ and amide bonds of proteins, which improves the solubility of Zn 2+ in the matrix and further contributes to the crosslinking reaction [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“… 46 In addition, the AMP in the NRL-GI-AMP film is a protein with a short-chain structure and has an antiaging effect, so the heat resistance of the NRL-GI-AMP film is higher than that of the NRL-GI film. 47 Zhan et al ( 48 ) reported that the addition of soy protein to natural rubber can promote the construction of a vulcanization network, increase the rigidity of the rubber, and reduce the breakage of the rubber chain.…”
Section: Resultsmentioning
confidence: 99%
“…28 However, the insignificant change in strain values after the irradiation might likely be due to the presence of proteins in NR, which limit the compactness of the rubber network. 29 Based on these results, the crosslinking process under vacuum could be enhanced by preserving the irradiated blend and preventing oxidative degradation in vulcanized NR/SIS blend films. Ambient oxygen primarily participates in the radical termination process, 30 while oxygen facilitates oxidative degradation through a peroxide radical mechanism.…”
Section: Gel Content Crosslink Density Thermal and Mechanical Propert...mentioning
confidence: 96%
“…A similar synergistic effect between non-rubber and rubber components has been found previously. 29 The 13 C-NMR spectra were recorded to analyze the chemical structure based on carbon groups of the neat NR and NR/SIS blends. As shown in Figure 6, the carbon signals detected at δ = 32.23, 135.16, 125.03, 26.38, and 23.4 ppm corresponded to C1, C2, C3, C4, and C5 of cis-1,4-PI.…”
Section: Monitoring Chemical Structure and Crystallinity Of Vulcanize...mentioning
confidence: 99%